Characterization of the novel HLA‐B*49:39 allele identified in a German leukaemia patient. (12 February 0002) - Becker, P. S. A.; Lindner, S.; Kim‐Wanner, S.‐Z.; Bug, G.; Seidl, C.
Abstract : HLA‐B*49:39 allele is characterised by 1 amino acid substitution in the alpha 1 domain.